The impacts of technological changes and regulatory frameworks on global air pollutant emissions from the energy industry and road transport. (September 2022) - Oreggioni, G.D.; Mahiques, O.; Monforti-Ferrario, F.; Schaaf, E.; Muntean, M.; Guizzardi, D.; Vignati, E.; Crippa, M.
Abstract: Despite the positive impacts of mitigation policies, air pollution is still a global issue of concern. This article builds on data presented in EDGAR (Emissions Database for Global Atmospheric Research) v5.0 database, exploring the influence of technology and regulation incorporation on air pollutant (NOx, PM2.5, SOX, NH3 ) emissions in the European Union (including the UK) and China. EDGAR results show that emissions from road transport and energy industries have significantly decreased between 1985 and 2015 in the European Union while on the contrary, driven by an increasing demand, emissions significantly increased in China between 1990 and 2005, followed by relevant reductions. This study evaluates the effectiveness of the key sectorial policies: pre-EURO 6 standards and the 2002 Large Combustion Plant Directive in the EU and the latest changes to Chinese legislation on emissions from energy industries and road transport. The outcomes of this work will provide useful information for policy design, monitoring and evaluation in these countries and in other regions, currently developing appropriate emission control measures. Possible trade-offs between climate change and air mitigation policies – such as the deployment of bioenergy systems and PM2.5 emissions – are also analysed as the impact of diesel fuelled vehicles on air quality. Highlights: Since 1985, EU and China have implemented emissions reduction policies. Retrospective scenarios were carried out to study their actual impact. Policies implemented policies have been effective in abating pollutants. Trade-offs with climate change policies have been also identified. Emission databases like EDGAR are crucial to evaluate policy efficacy.